Data from: Modelling bat distributions and diversity in a mountain landscape using focal predictors in ensemble of small models ... - Scherrer, Daniel; Christe, Philippe; Guisan, Antoine (Dryad, 2020)
Aim: Bats are important components of mammalian biodiversity and strong bioindicators, but their fine scale distributions often remain less known than other taxa (e.g. plants, birds). Yet as highly mobile species with multiple needs in the landscape, bats impose serious modelling challenges, such as advanced use of neighbourhood analyses. The aims of this study were to test the use of a designed sampling of bats for biodiversity and conservation assessments, and to find appropriate modelling solutions for providing nature practitioners with reliable potential bat distribution maps in a mountain area of high conservation interest . Location: The western Swiss Alps of Vaud Methods: We conducted a one-year field survey combining passive acoustic recordings supplemented by mist net catching to collect data on bats. These data were then used to create univariate models with focal land use/cover variables using different focal window sizes to detect the optimal species specific scale of influence for each ... : Data used for modellingThis archive contains the processed data used for modelling.Raw occurence dataThis file contains the data from both the acoustic sampling and capture of bats with additional information about locations, field experts and bio-metric data of the bats. ...